APPLICATION OF EPSILON METHOD TO MODELING EXPECTATIONS IN CONSTRUCTION - Nehrebecka, Natalia; Grodkowska, Sylwia (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
The epsilon method has been applied to examine the strength ofrelations among selected objective and subjective factors connected with amanager’s predictions of their companies’ development. The aim of this research was to study which variable has the strongest impact on business expectations in construction. The results offer compelling evidence that respondents rely both on their current opinion on enterprise as well as on generaleconomic situation. The survey was carried out based on Polish data from2000:1 to 2008:10